Vagus nerve stimulation potentiates hippocampal LTP in freely-moving rats - Zuo, Yantao; Smith, Douglas C.; Jensen, Robert A. (Physiology & behavior, 2007)
Previous studies have demonstrated that electrical stimulation of the vagus nerve (VNS) delivered at a moderate intensity following a learning experience enhances memory in laboratory rats and human subjects, while VNS at lower or higher intensities has little or no effect. This finding suggests that VNS may affect memory processes by modulating neural plasticity in brain structures associated with memory storage such as the hippocampus. To test this hypothesis, the present study investigated the modulatory effect of VNS on the development of long-term potentiation (LTP) in the dentate gyrus of freely-moving rats. Rats receiving 0.4 mA VNS showed enhanced potentiation of the population spike amplitude for at least 24 h after tetanus relative to the sham-stimulation group. In contrast, no such effect was observed with 0.2 mA VNS. Stimulation at 0.8 mA had a short-term effect and tended to enhance early LTP, but to a lesser extent than did 0.4 mA. The 0.4 mA stimulation was the same intensity that was previously shown to enhance retention performance in an inhibitory avoidance task. These findings suggest that the neural mechanisms underlying the mnemonic effect of VNS may involve modulating synaptic plasticity in the hippocampus. These data also suggest that neural activity in the vagus nerve, occurring as a result of changes in peripheral state, is an important mechanism by which emotional experiences and arousal can enhance the storage of memories of those experiences.